PRELIMINARY RODENT CONTROL PROGRAM IN BANDAR ABBAS, SOUTHERN IRAN - F. Djafari; M. Asmar (Tehran University of Medical Sciences, 1986)
A general rodent control program was carried out in Bandar Abbas in the Persian Gulf (15 Sep-22 Oct 1984). Researches on the variety of the rodents and their parasites were done and Zincphosphide and Comatetralil baits were used for in-doors and out-doors. Results obtained showed that these campaigns were successful.